Relevansi Sekolah Terbuka terhadap Pemikiran Ivan Illich tentang Pendidikan dalam Deschooling of Society - Fiky Arista; Rhoma Dwi Aria Yuliantri (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study is motivated by the state of education in Indonesia, which remains inaccessible to all segments of society facing various limitations. Ivan Illich’s book Deschooling Society introduces a new perspective: that education is not limited to formal schools but is also acquired through the environment and habits formed from an early age. The book was written against a social backdrop that closely mirrors the state of education in Indonesia. The research method employed for this article is descriptive qualitative. The sources used for this research include literature reviews, interviews, and Ivan Illich’s book Deschooling of Society. Data analysis employs the Miles and Huberman interactive model. This article demonstrates the relevance between Ivan Illich’s ideas and open schools. Open schools serve as a solution for students who have dropped out due to economic constraints, limited transportation, and a social and cultural environment that does not support access to education. Open schools offer flexible learning schedules—conducted on specific days—while still granting the same diplomas as formal schools. The educational monopoly criticized by Ivan Illich in his book can be addressed through the existence of open schools. Although there are differences in practice—such as Ivan Illich’s rejection of diploma recognition, the abolition of formal education, and the methods used in learning—open schools provide a viable alternative.